Over a million students use our free study notes to help them with their homework
dy/dx = 2xcos(x2+2)
Using the chain rule, we know that dy/dx = dy/dt . dt/dx Therefore we differentiate both equations with respect to t:dx/dt = -4dy/dt = -2/(t^2)therefore dy/dx = -1/4 . -2/(t^2)dy/dx = 1/(2t^2) ... (we kno...
tan(x) is defined as sin(x)/cos(x) For a function which can be written as f(x) = u(x)/v(x) the quotient rule can be appliedThe quotient rule states f ' (x) = (u'v-v'u)/v^2 Applying this to the formula for...
Firstly, integrate y with respect to dx. Increase the powers of x by 1 and then divide the coefficient of x by the new power of x. I.e.: x^3 becomes 1/4x^4. The power increases from 3 to 4 and the coeffic...
The Chain-rule is used to differentiate a function of a function. Running through an example:Let's say want to differentiate the function y = (2x+1)^3. We can substitute a variable, w, in order to differe...
←
222
223
224
225
226
→
Internet Safety
Payment Security
Cyber
Essentials